Performance of Alpha Fetoprotein in Combination with Alpha-1-acid Glycoprotein for Diagnosis of Hepatocellular Carcinoma Among Liver Cirrhosis Patients - Rino A Gani; Maulana Suryamin; Irsan Hasan; C. Rinaldi A Lesmana; Andri Sanityoso (Acta Medica Indonesiana)
Aim: to evaluate the use of alpha-1-acid glycoprotein (AAG) for diagnosing hepatocellular carcinoma (HCC), and to combine with alpha fetoprotein (AFP) as part of routine examination in liver cirrhosis patients. Methods: this is a diagnostic study using cross-sectional design. A hundred and six patients were included in this study. Baseline data such as age, gender, AFP, AAG, peripheral blood count, AST and ALT were consecutively collected from liver cirrhosis patients with or without HCC. Serum AAG were measured quantitatively using immunoturboditimetric assay and AFP with enzyme immune assay (EIA). Statistical analysis were done using SPSS 13.0. Data comparisons between group were done using Mann-Whitney test. Diagnostic performance for each marker alone was compared to the surrogate use of both markers (combined parallel approach) in HCC cases. Results: receiver operating characteristic (ROC) analysis showed that area under the curve for AFP AAG combination was 88.1% and higher than AFP only (86.2%) or AAG only (76.5%) with sensitivity of 83%, 73% and 44%, respectively, at specificity of >80%. Conclusion: our study showed that combination of AFP and AAG is superior than either marker alone in diagnosing HCC in liver cirrhosis patients. Combination of AFP and AAG may be used to prompt early diagnosis screening of HCC.